2021
DOI: 10.1186/s12931-021-01752-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bilateral lung transplantation on cardiac autonomic modulation and cardiorespiratory coupling: a prospective study

Abstract: Background Although cardiac autonomic modulation has been studied in several respiratory diseases, the evidence is limited on lung transplantation, particularly on its acute and chronic effects. Thus, we aimed to evaluate cardiac autonomic modulation before and after bilateral lung transplantation (BLT) through a prospective study on patients enrolled while awaiting transplant. Methods Twenty-two patients on the waiting list for lung transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A study did not find any differences between SSc subsets [ 28 ], while two studies found a reduced HRV total power in dcSSc compared to lcSSc [ 14 , 15 ]. The reduced HRV total power should be compatible with a cardiac autonomic dysfunction from both branches of the autonomic nervous system as observed in other rheumatologic [ 29 , 30 ] and cardiopulmonary [ 31 , 32 ] diseases.…”
Section: Discussionmentioning
confidence: 71%
“…A study did not find any differences between SSc subsets [ 28 ], while two studies found a reduced HRV total power in dcSSc compared to lcSSc [ 14 , 15 ]. The reduced HRV total power should be compatible with a cardiac autonomic dysfunction from both branches of the autonomic nervous system as observed in other rheumatologic [ 29 , 30 ] and cardiopulmonary [ 31 , 32 ] diseases.…”
Section: Discussionmentioning
confidence: 71%
“…HRV is closely regulated by the central autonomic network involving brainstem, prefrontal cortex, limbic system, and other higher-order brain structures. To note, a shift of the autonomic balance toward a sympathetic predominance has been associated with a higher risk of mortality (Tsuji et al, 1996;Malliani and Montano, 2002), and highlighted as a prognostic marker of adverse clinical outcome in cardiopulmonary (Tobaldini et al, 2020(Tobaldini et al, , 2021, neurodegenerative (Carandina et al, 2022;Lazzeri et al, 2022) and autoimmune (Rodrigues et al, 2019(Rodrigues et al, , 2022 diseases. In recent years, the study of HRV has found increasingly wide applications, opening up fascinating research fields in various neurological and neuropsychiatric disturbances.…”
Section: Heart Rate Variability Analysis As a Methods For Assessing C...mentioning
confidence: 99%